Level of prevention against the crime of extortion and citizen security - Huaman-Ruiz, Lesvy (2024)
This research aims to evaluate the level of prevention against the crime of extortion and its influence on citizen security in the city of Lima. The research is of an applied type, evaluative level and the design is non-experimental since the study variables were not manipulated. The population was made up of magistrates and citizens, the sample was represented by 10 Criminal Judges, 19 Criminal Prosecutors and 31 lawyers specialized in Criminal Law from the Judicial District of Lima; The technique applied was the survey and the instrument was the questionnaire, validated by experts in the area. As results, it is shown with a level of significance a= 0.05 (with 95% confidence), that the level of communication and dissemination in the prevention of the crime of extortion, the level of knowledge about risk issues and the management of security strategies significantly influence citizen security in the city of Lima. It is concluded that the level of prevention against the crime of extortion significantly influences citizen security in the city of Lima.